2002
DOI: 10.3758/bf03196271
|View full text |Cite
|
Sign up to set email alerts
|

Vantage point in episodic memory

Abstract: Universityundergraduates undertook a seriesof manual tasks (e.g., shaping objects out of clay) and later recalled the experiences they had while doing so from either a field or an observer vantage point. In the former case, the subjects mentally reinstated the original task environment as if they were seeing it again through their own eyes; in the latter condition, the original task environment was envisioned from the perspective of a detached spectator. Analysis of the subjects' recollectionsrevealedmarked di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
183
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(197 citation statements)
references
References 15 publications
9
183
1
2
Order By: Relevance
“…Imagery perspective has shown to influence what is recalled (McIsaac & Eich, 2002), processing style 2 We also hypothesized differential activity for field and observer perspective in the amygdala. As activation in these structures are commonly in a small voxel range, we performed a ROI-analysis using a mask of the left and right amygdala according to the Talairach coordinates (Talairach & Tournoux, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Imagery perspective has shown to influence what is recalled (McIsaac & Eich, 2002), processing style 2 We also hypothesized differential activity for field and observer perspective in the amygdala. As activation in these structures are commonly in a small voxel range, we performed a ROI-analysis using a mask of the left and right amygdala according to the Talairach coordinates (Talairach & Tournoux, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Imagery perspective can influence the information that is recalled about events and the intensity of the emotional response. Previous research has indicated that individuals imagining memories from a field perspective gave more statements concerning affective reactions, physical sensations, and psychological states, whereas memories imagined from an observer perspective included more information concerning how the person looked, physical actions, or spatial relations (McIsaac & Eich, 2002). It has also been proposed that thinking about past events in terms of the experiences evoked by features of the event is related to a field perspective, as compared to thinking about the event in terms of its broader context or meaning in an individuals' life which is related to an observer perspective (Libby & Eibach, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…People can re-experience an event by remembering it with others and details may be added or removed, with little or no consequence (McIsaac & Eich, 2002). However, there are times when remembering needs to be accurate (e.g., in criminal investigations).…”
mentioning
confidence: 99%